Moralitas dan Spiritualitas Islam Sebagai Arah Reformasi Pendidikan - Kusrini, Siti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
To face the challenge of globalization era, moslems in Indonesia begin to have sympathy and moral obligation, since Islam is a teaching that becomes hudan (guidance) toward the reforms of all aspects of life. It expects a society, the supremacy of which, is in God's hand. While the human being must surrender to and worship to God. To face the 21st century, Islamic ethics and moral are required to create the expected civilized society. Therefore, the moslems must be able to identify the dimension of ethical and social values that can guide its followers to conduct moral reasoning or ijtihad, in order to realize the development of the expected civilized society.